High Mobility Group Box 1 Contributes to the Acute Rejection of Liver Allografts by Activating Dendritic Cells - Chen, Yi; Zhang, Wenmin; Bao, Hui; He, Wubing; Chen, Lihong (Frontiers in Immunology, 2021)
Acute rejection induced by the recognition of donor alloantigens by recipient T cells leads to graft failure in liver transplant recipients. The role of high mobility group box 1 (HMGB1), an inflammatory mediator, in the acute allograft rejection of liver transplants is unknown. Here, rat orthotopic liver transplantation was successfully established to analyze the expression pattern of HMGB1 in liver allografts and its potential role in promoting the maturation of dendritic cells (DCs) to promote T cell proliferation and differentiation. Five and 10 days after transplantation, allografts showed a marked upregulation of HMGB1 expression accompanied by elevated levels of serum transaminase and CD3+ and CD86+ inflammatory cell infiltration. Furthermore, in vitro experiments showed HMGB1 increased the expressions of co-stimulatory molecules (CD80, CD83, and MHC class Ⅱ) on bone marrow-derived DCs. HMGB1-pulsed DCs induced naive CD4+ T cells to differentiate to Th1 and Th17 subsets secreting IFN-γ and IL-17, respectively. Further in vivo experiments confirmed the administration of glycyrrhizic acid , a natural HMGB1 inhibitor, during donor liver preservation had therapeutic effects by reducing inflammation and hepatocyte damage reflected by a decline in serum transaminase and prolonged allograft survival time. These results suggest the involvement of HMBG1 in acute liver allograft rejection and that it might be a candidate therapeutic target to avoid liver transplantation.